Taxation and the Financial Crisis - Julian S. Alworth; Giampaolo Arachi (Oxford University Press, 2012)
The financial crisis has opened up a global debate on the taxation of the financial sector. A number of international policy initiatives, most notably by the G20, have called for major changes in the tax treatment of financial institutions and transactions as well as individuals working in the financial sector. This book examines how tax policies contributed to the financial crisis and whether taxation can play a role in the reform efforts under way to establish a sounder and safer financial system. The book looks at the pros and cons of various tax initiatives, including limiting the tax advantages to debt financing, special taxes on the financial sector and financial transactions taxes.
Keywords: 330; Tax policy; Financial crisis; Taxation; Debt financing; Financial sector